Determinant Factors of Pneumonia among Toddlers - Muchsin Maulana; Dwi Rahmatun Handari; Septian Emma Dwi Jatmika; Hermin Sunarti (International Journal of Public Health Science (IJPHS), 2018)
Pneumonia still becomes a public health problems that causing pain and death on toddlers. There are many factors which may influence the increase of pneumonia incidence on toddlers, from the aspect of kid individuals and house anvironment such as ventilation, residential density and the presence of smokers. In 2016 found 760 cases of pneumonia that took place in Yogyakarta Country. One area of this district with high influence of pneumonia is Public Health Center of  Gondomanan, this area increased the number of pneumonia incidence in 2014-2016. This research used Cross Sectional research design with Chi Square analysis. The sample of this research is 54 respondents were obtained by Purposive Sampling technique. Instrument is used questionnaired to measure ventilation, residential density and the presence of smokers observation. Showed that there was a correlation between ventilation (p=0.000; RP=2.786), residential density (p=0.007; RP=2.043), the presence of smokers (p=0.002; RP=2.2) with pneumonia incidence on toddlers, in the Area of Puskesmas Gondomanan, Yogyakarta. Ventilation, residential density, and the presence of smokers is Correlation with pneumonia incidence on toddlers in one area of Yogyakarta.